Analysis of loco-regional and distant recurrences in breast cancer after conservative surgery. Issue 1 (December 2016) - Elsayed, Mostafa; Alhussini, Mahmoud; Basha, Ahmed; Awad, A.
Abstract Background A number of patients treated conservatively for breast cancer will develop loco-regional and distant recurrences. Our aim was to determine how their occurrence may be linked to the evolution of the disease. Methods We analyzed 238 women treated by conservative breast surgery and breast irradiation in a single institution. We evaluated the prognostic factors associated with loco-regional and distant recurrences and the prognostic value of local and regional recurrences on systemic progression. Results After a median follow-up of 5 year (range 1–10), 16 (6.72 %) patients in the breast conservative surgery (BCS) groups had loco-regional recurrence. For distant recurrence, 10 (4.2 %) patients had experienced distant recurrence. Lympho-vascular invasion (HR 2.55; 95 % CI, 076 to 8.49) and an extensive intraductal component (HR, 2.22; 95 % CI, 0.69 to 7.15) and nodal status are risk factors for loco-regional recurrence (LRR) after breast conservative therapy (BCT). Tumor size, nodal status, high histologic grade, and breast cancer diagnosed at a young age (≤35 years) are correlated with higher distant recurrence rates after BCT. Conclusions Risk factors for LRR after BCS include lympho-vascular invasion, extensive inraductal component, and high nodal status, where as risk factors for distant recurrence include tumor size, nodal status, high histologic grade, and breast cancer diagnosed at a young age (≤35 years).